419 HISTORICAL CLINICAL EXPERIENCE OF SKIN CANCER DEVELOPMENT IN LONG TERM ORGAN TRANSPLANT RECIPIENTS. (1st January 2005) - Weber, M.; Johnson, K.; Osgood, M.; Trotter, J.; Hartmann, N.; Starzl, T.; Pacheco, T.
Abstract : Purpose: Colorado has a unique transplant history, as The University of Colorado (UC) was the setting for pioneering work in solid organ transplantation under the direction of Thomas Starzl, M.D., Ph.D in the early 1960s. Because of the widespread use of immunosuppressive therapy, many of these early transplant recipients are still alive and have been followed in the Dermatology clinic at UC. However, this group of patients is not included in current statistical registries and there are no reports that have examined the development of skin cancer in long term organ transplant recipients (OTRs) that were transplanted an average of over thirty years ago. In this case series, we identify and contact an aged group of kidney and liver OTRs in an attempt to assess their incidence of non-melanoma skin cancer (NMSC). Methods: 53 aged original Starzl transplant recipients were identified in the "World Transplant Records." (Cecka, Terasaki Clinical Transplants 2002) This reference lists the longest transplant survivors and contains records of patients who currently have functioning transplants. Individuals were contacted by writing or telephone and invited to participate in the IRB approved, HIPPA compliant survey. They were asked to fill out a questionnaire aimed to assess transplant history, medication history, and numerous questions regarding skin disease and NMSC risk factors. Results: 22/53 individuals responded to the survey. The mean years of transplant function in this series was 32 (range 18-41), with a mean 23 years of immunosuppression (range 0-38). Nine of 22 developed NMSC post-transplant. Eight of 14 kidney OTRs developed NMSC, with six of these reporting ≥2 SCC's. Of note, NMSCs resolved in several kidney OTRs after tapering off immunosuppressive therapy. Conclusions: This case series highlights some of the longest surviving OTRs in the world. Although the numbers are small, our results suggest it is reasonable to attempt medication weaning. While not complete, the current registries of this unique population offer us valuable information and deserve further examination. An increased amount of data on NMSC in long term OTRs will allow for identification of both critical risk factors and key determinants of skin cancer in OTRs, thereby aiding transplant and dermatology physicians in developing transplant/skin protocols to advance the care of these patients.